Common Errors Identification in Pronouncing Silent Letters in English Words by EFL Novices - Ali Mohammed Saleh Al-Hamzi; Lilla Musyahda (PAROLE: Journal of Linguistics and Education, 2022)
In English, the sound system is somewhat distinct from Arabic. Yemeni Novices have many difficulties pronouncing English terms owing to this. For example, we often hear English learners pronounce "sight [sait]" with "[saig]" or "know,” [nəʊ]" with "[knəʊ]." This study is concerned with identifying widespread errors in the pronunciation of silent letters in English words among Yemeni EFL learners. Qualitative descriptive study was used in this investigation as a methodology. With the aid of purposive sampling techniques, a sample of 5 EFL novices was selected from 1st level of the English Department, Faculty of Education, Sana'a University, Yemen, which was classified into a group of novice high-level learners (beginners). Analytically descriptive method was used to analyze the data after they were collected through test. The result of this study showed that in pronouncing words containing the silent letters like b, c, d, g, gh, h, k, l, m, n, p, s, t, th, and w, the researcher finds errors made by the EFL novices. He analyzes three positions of the silent letters in the words (initial, medial, and final position) and by understanding this; it would be possible to develop useful instructional materials and teaching strategies to target this issue.